A közép-kelet-európai lakásrendszerek átalakulása (Szociológiai Szemle, 2024)
This paper gives an overview on the potential directions of restructuring of the East European Housing Model and discusses the factors influencing the choice between these directions. Despite the mass privatization of the state rental stock, there is no evidence in the East-Central-European countries of a clear market orientation of the housing system. There are strong political and institutional interests existing which demand - a special housing system, dominated by the non-market type of private sector. The real market-oriented restructuring of the housing system can only be carried out parallel to the real modernization of the economic, social and political systems.